Cellulose Nanocomposites for High-Performance Applications - Cherian, Bibin Mathew [UNESP]; Leao, Alcides Lopes [UNESP]; Souza, Sivoney Ferreira de [UNESP]; Thomas, Sabu; Pothan, Laly A.; Kottaisamy, M.; Kalia, S.; Kaith, B. S.; Kaur, I (Springer, 2011)
Cellulose nanofibers and their composites offer a highly attractive research line in recent times. Cellulose nanolibers have generated a great deal of interest as a source of nanometer-sized fillers because of their sustainability, easy availability, and the related characteristics such as a very large surface-to-volume ratio, outstanding mechanical, electrical, and thermal properties. This chapter describes the many processes to produce nanocellulose from different cellulosic sources and how to increase the compatibility between cellulosic surfaces and a variety of plastic materials. Furthermore, it provides knowledge of different nanocelluloses and nanocomposites and provides updated information on their properties and also deals with fascinating high-tech applications, especially in the medical field.
Keywords: Cardiovascular tissues; Cosmetic tissues; Medical applications; Meniscus implant; Nanocelluloses; Nanocomposites; Veterinary medicine